Study of thin-walled cold-formed framework with semi-rigid connection - Seah, Leong Keey. (2008)
The behaviour of symmetrical single and double-storey frameworks, constructed from cold-form thin-walled plain channel memebrs and semi-rigid connections, is investigated both analytically and experimentally.